Backernagel is Wackernagel Lite. On the “P-Minus 2” Clitics of Santali - Hock, Hans Henrich (Lingua Posnaniensis, 2013)
Santali presents structures with subject clitics in “P minus 2” (P-2) position, before the final verb and enclitic on the preverbal element, a position called “Backernagel” by Kidwai (2005). P-2 is commonly considered to lack clear cross-linguistic support; moreover, while generative accounts can accommodate utterance-second position (P2) as adjunction to a left-peripheral projection, they have no ready way of accommodating P -2. The history and synchrony of Munda “P-2” have elicited several accounts. Anderson (2007) considers three possibilities: Reanalysis of P roto-Munda subject proclitics as enclitic; extension of postverbal object clitics to preverbal subject function; attachment of original resumptive pronouns to the preverbal element. I present evidence for a different hypothesis: T he Santali Backernagel clitics originate as P 2 or classical W ackernagel elements. A more fine-grained definition of W ackernagel in terms of different prosodic domains (such as utterance/theme vs. rheme) permits the hypothesis that the apparent P -2 is still a W ackernagel position, but within the rheme rather than the entire utterance, and that within the rheme, the prosodically strongest, preverbal-focus element is the most attractive clitic host. I support my account with evidence from Santali and other K herwarian languages (which offer traces of an original P 2 position) and parallel developments in Iranian (where the different stages in the development can be traced in greater detail). Backernagel, thus, is a subtype of W ackernagel, and there is no need to assume a typologically problematic P -2 position for Munda (or for various Iranian varieties).